Application of The Problem Based Learning Model in Indonesian Language Learning Class IX E at SMPN 1 Diwek - Rika Sari Solikah; Arisni Kholifatu Amalia Shofiani (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
This research was conducted with the aim of exploring the effectiveness of using the problem based learning model on Indonesian language learning outcomes for student in grade IX E at SMPN 1 Diwek, Jombang Regency. Researchers found problems in Indonesian language learning implemented by teachers which were still conventional, this factor also had the potential to influence student learning achievement thus, the learning model needs to be updated to achieve success in implementing teaching and learning activities. This research is a qualitative study using field methods, where researchers are directly involved in observations, both regarding the teaching and learning process and conditions in the school. The data collection methods applied include observation, interviews and documentation. The research subjects were students in class IX E at SMPN 1 Diwek Jombang with a total of 31 students and Indonesian language teachers in class IX E. Data analysis in this research included the stages of data collection, data reduction, data presentation and drawing conclusions. The results of this research are that after implementing the problem based learning model on class IX E students, students showed increased contextual understanding through active participation in problem solving, critical thinking, analyzing problems collaboratively, student involvement in increasing their motivation and involvement in the process of learning Indonesian language By implementing a problem-based learning model, it is very effectively implemented in class IX E of SMPN 1 Diwek Jombang.